2019
DOI: 10.1016/j.foodchem.2019.125026
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic, oxylipin and fatty acid profiles of the Chilean hazelnut (Gevuina avellana): Antioxidant activity and inhibition of pro-inflammatory and metabolic syndrome-associated enzymes

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 36 publications
1
51
0
Order By: Relevance
“…In the present, only a few studies on PhytoPs in almonds, nuts, and olives have been reported ,,,, and scarce relationships have been established between agricultural practices like water management and these plant oxylipins. We hypothesize that water constrains/water stress leads to the synthesis of phytoprostanes and phytofurans on almonds and that such bioproducts may serve as indicators of water stress.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In the present, only a few studies on PhytoPs in almonds, nuts, and olives have been reported ,,,, and scarce relationships have been established between agricultural practices like water management and these plant oxylipins. We hypothesize that water constrains/water stress leads to the synthesis of phytoprostanes and phytofurans on almonds and that such bioproducts may serve as indicators of water stress.…”
Section: Introductionmentioning
confidence: 84%
“…41 Besides being reliable biomarkers of OS, PhytoPs and PhytoFs are also lipid mediators. 39 PhytoPs have many health benefits such as (i) protecting cells against the damage produced under OS conditions, playing an important role in the immune and neuronal function regulation; (ii) interacting with gut microflora; and (iii) developing anti-inflammatory and apoptosis-inducing activities and (iv) as anti-oxidants 7,21,29,42−44 These actions have been recently associated with the structural similarities of PhytoPs and PhytoFs vs human oxylipins 44−46 In the present, only a few studies on PhytoPs in almonds, nuts, and olives have been reported 7,8,13,14,47 and scarce relationships have been established between agricultural practices like water management and these plant oxylipins. We hypothesize that water constrains/water stress leads to the synthesis of phytoprostanes and phytofurans on almonds and that such bioproducts may serve as indicators of water stress.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This experimental design allowed providing further insights into the specific inflammatory modulation of individual PhytoPs and PhytoFs by evaluating changes in the intracellular and extracellular concentration of the 7 PGs found in quantifiable amounts in THP-1 cells (15-keto-PGF 2α , PGF 2α , 11β-PGF 2α , PGE 2 , PGD 2 , PGDM, and PGF 1α ). Also, this work provides new complementary information with respect to previous descriptions of the biological functions of PhytoPs and PhytoFs, focused on the cytokines profile and/or the phenotype of immune-cells through earlier works which focused on a single plant oxylipin or complete plant extracts of PhytoPs and PhytoFs [30,34,[57][58][59][60][61]. In this regard, the use of whole extracts constitutes an approach that allows retrieving valuable results, but is limited in scope.…”
Section: Modulation Of the Inflammatory Response-mediated Through Intracellular Prostaglandins By Plant Oxylipins After Lps-induced Inflamentioning
confidence: 99%
“…Fatty acid methyl ester (FAME) derivatization was achieved using the AOAC 969.33 protocol for fatty acids [22] with Myristic-d-27 acid (75 mg/L) as the internal standard. The GC-MS analysis was performed using a 30 m × 0.25 mm × 0.2 µm ionic liquid SLB-IL-111 column from Supelco.…”
Section: Analysis Of Fatty Acid Profilementioning
confidence: 99%